Metafora Ontologis serta Skema Citra pada Lagu Religius “Al-Ḥamdu lillāh” dan “Rūḥī Fidāk” Mesut Kurtis: Kajian Semantik Kognitif - Muhamad Hendriawan; Fahmy Lukman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Religious song lyrics frequently employ metaphorical language to represent spiritual and emotional experiences in a conceptual manner. Yet studies specifically examining ontological metaphors and image schemas in religious lyrics, particularly those of Mesut Kurtis, remain relatively scarce. This study aims to identify the forms of ontological metaphor, analyze the types of image schema, and explain the conceptualization patterns found in the lyrics of Al-Ḥamdu lillāh and Rūḥī Fidāk. A qualitative descriptive approach was applied, with data collected through the observational reading method and note-taking technique. Data analysis drew upon the conceptual metaphor theory proposed by George Lakoff and Mark Johnson, as well as the image schema theory developed by Cruse and Croft. The findings indicate that seven forms of ontological metaphor were identified, representing abstract concepts such as emotions and inner states as concrete entities. Several image schema types were also found, namely space, container, force, and existence, with the container schema emerging as the most dominant pattern. These findings demonstrate that the conceptualization of meaning in Mesut Kurtis's lyrics is shaped by embodied experience, which plays a constitutive role in forming conceptual understanding of the religious and emotional experiences expressed therein.